Weddell-Scotia Confluence Effect on the Iron Distribution in Waters Surrounding the South Shetland (Antarctic Peninsula) and South Orkney (Scotia Sea) Islands During the Austral Summer in 2007 and 2008 - Sanchez, Nicolas; Reiss, Christian S.; Holm-Hansen, Osmund; Hewes, Christopher D.; Bizsel, Kemal C.; Ardelan, Murat V. (Frontiers in Marine Science, 2019)
An oceanographic survey around the South Shetland Islands (SSI) and the South Orkney Islands (SOI) was conducted during January 2007 and February 2008, respectively, as part of the United States Antarctic Marine Living Resources program ecosystems surveys. At 27 stations, concentrations of dissolved labile (DFe) and total acid leachable (unfiltered, TaLFe) iron (Fe) were measured in the upper 200 m (including coastal and oceanic waters) to better resolve the factors limiting primary production in these regions. Northwest of the SSI, a region influenced by Drake Passage waters, mean DFe (~0.26 nM) and TaLFe (~1.02 nM) concentrations were the lowest, whereas intermediate concentrations for both DFe and TaLFe were measured in the Bransfield Strait. Around Elephant Island, over and off the continental shelf, Fe concentrations differed between the west and the east margins. DFe and TaLFe concentrations further support the argument that the effect of the Shackleton Transverse Ridge is a crucial structure affecting both the Fe and the chlorophyll distributions in this region. The waters around the SOI had DFe concentrations higher than those in the SSI, with the area north of the South Scotia Ridge (60ºS), having the highest DFe (0.54 nM) concentrations and the waters in Powell Basin having the lowest DFe (1.17 nM) and TaLFe (4.51 nM) and concentrations. These spatial patterns of Fe suggest that there are different Fe inputs from shelf waters near the Antarctic Slope Front. The overall TaLFe:DFe ratios, used as indicator for understanding the relative distance of Fe sources, were lower around the SOI compared to those in the SSI, suggesting that the Fe source for SOI waters was more distant. The spatial patterns between Fe and chlorophyll-a concentrations in relation to the hydrography, highlight the complexity and variability of the oceanographic processes in the region. These results improve the knowledge on the Fe sources and inputs in the less known SOI waters during the austral summer, and they further support the importance of advective processes from the Fe-rich waters that flow from the eastern margin of the Antarctic Peninsula into the Weddell-Scotia Confluence.